Language, multiple authenticities and social media: The online language practices of university students in Mongolia. (10th August 2015) - Dovchin, Sender
<x xml:space="preserve">Abstract</x> This paper seeks to contribute to the current discussion of the sociolinguistics of globalization by revealing youth linguistic diversity from the perspective of the online mixed language practices of university students in contemporary post‐socialist Mongolia. Drawing on sets of Facebook data, the paper firstly argues that the online mixed youth language practices should be understood as 'translingual' not only due to their varied recombination of linguistic and cultural resources, genres, modes, styles and repertories, but also due to their direct subtextual connections with wider socio‐cultural, historical and ideological meanings. Secondly, online users metalinguistically claim authenticity in terms of their own translingual practices as opposed to other colliding language ideologies such as linguistic dystopia. How they relocalize the notion of authenticity, however, differs profoundly depending on their own often‐diverse criteria, identities, beliefs and ideas. This shows that, with mixing and recombining at its very core, the translingual practices of modern young speakers provide us with a significant insight into the co‐existence of multiple authenticities and origins of authenticity in an increasingly interconnected world.